An experimental study of the injection strategies on engine performance of the butanol/biodiesel dual-fuel Intelligent Charge Compression Ignition mode. (October 2021) - Zhao, Wenbin; Zhang, Yaoyuan; Huang, Guan; Li, Zilong; Qian, Yong; He, Zhuoyao; Lu, Xingcai
Intelligent Charge Compression Ignition (ICCI) combustion mode is a novel dual-fuel combustion strategy that has been proposed recently. In ICCI combustion mode, two fuels with different reactivity are directly injected during the intake stroke and compression stroke, respectively, to achieve flexible reactivity gradient and equivalence ratio stratification. In this study, experiments were conducted on a single-cylinder diesel engine to investigate the effects of butanol direct injection strategies on the engine running with ICCI combustion mode at a constant speed of 1500 r/min and medium load. Results showed that ICCI combustion mode was composed of premixed heat release and diffusion heat release. In compare, the percentage of premixed heat release was higher than the diffusion heat release. With fixed biodiesel direct injection timing (SOI2), retarding butanol single injection timing (SOI1) would delay combustion phasing while not distinctively affect ignition timing. SOI1 showed significant effect on the thermal efficiency and engine emissions. Indicated thermal efficiency (ITE) decreased at first and then slightly increased with retarding of SOI1, while the nitrogen oxides (NOx) emissions were always at low levels. As the butanol second direct injection timing (SOI1-2) retard and the corresponding energy ratio increase, more butanol entered into the crevice/squish regions, leading to the increase of unburned hydrocarbon (HC) and carbon monoxide (CO) emissions. EGR strategy helps to significantly reduce NOx emissions without affecting ITE although penalized HC and CO emissions are resulted in. The optimum butanol direct injection strategies were butanol single direct injection, especially in the early SOI1, in which the thermal efficiency was higher and emissions were at very low levels (NOx < 0.4 g/kW h).